The Paradigm of Meaningful Guilty Pleas: Balancing Procedural Efficiency and Substantive Justice in the Indonesian Criminal Justice System - Prasetyo, K. M. M. Gusti; Rivanie, Syarif Saddam; Karim, Muhammad Said; Latif, Birkah (SIGn Journal of Social Science, 2025)
This study is motivated by the systemic dysfunction of the Indonesian criminal justice system, characterized by case backlogs and overcrowding in correctional institutions. This condition prompted the adoption of the plea bargain mechanism in Article 78 of the New Criminal Procedure Code. However, the application of this special track potentially becomes trapped in procedural pragmatism that neglects the search for material truth and the essence of substantive justice. The objective of this study is to formulate the Meaningful Guilty Plea paradigm as a synchronization instrument between the procedural efficiency of Article 78 of the New Criminal Procedure Code and substantive justice values in the sentencing guidelines of Article 54 of the New Penal Code. The research method used is normative legal research, employing statutory, conceptual, and comparative approaches through qualitative-prescriptive analysis. The results indicate that plea bargain formalism requires a rigid material foundation so that granting sentence reduction is not speculative-transactional in nature. The construction of the meaningful guilty plea paradigm requires examining the quality of the defendant’s statement, based on indicators of sincere remorse, moral responsibility, and commitment to victim recovery, to ensure sentencing proportionality. This synchronization enables a transition from a retributive pattern to a restorative-corrective model, as mandated by the New Penal Code. The conclusion asserts that procedural efficiency must be governed by active judicial control, achieved through the integration of sentencing guidelines to prevent judicial decision-making disparities. This study recommends the formulation of implementing regulations in the form of sentencing guidelines that integrate the plea-bargaining mechanism nationwide as a crucial implementation step following the recent enforcement of the new criminal law on January 2, 2026. Under this ideal model, the criminal justice system is expected to achieve sustainable harmony between the speed of processes and the quality of decisions that are substantively just for both the defendant and the victim.